Nonaqueous electrolyte and lithium secondary battery containing same
Patent Information
- Application Number
- JP2024552044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-10-12
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2043-10-12
Smart Images

Figure 2025508518000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte and a lithium secondary battery containing the same. [Background technology]
[0002] In recent years, the application areas of lithium secondary batteries have been rapidly expanding from power supply for electronic devices such as electrical, electronic, communication, and computer devices to power storage and supply for large-area devices such as automobiles and power storage devices. Accordingly, there is an increasing demand for high-capacity, high-output, and highly stable secondary batteries.
[0003] In particular, high capacity, high output, and long life characteristics are important for lithium secondary batteries for automotive applications. To increase the capacity of secondary batteries, positive electrode active materials with high nickel content, which have high energy density but low stability, are used, or secondary batteries are operated at high voltage.
[0004] However, when a secondary battery is operated under the above conditions, as charging and discharging proceeds, the coating formed on the surface of the positive electrode / negative electrode or the structure of the electrode surface may deteriorate due to side reactions caused by the deterioration of the electrolyte, and transition metal ions may be eluted from the surface of the positive electrode. In this way, the eluted transition metal ions are electro-deposited on the negative electrode, which reduces the passivation ability of the SEI, causing the problem of the deterioration of the negative electrode.
[0005] This deterioration phenomenon of the secondary battery tends to be accelerated when the potential of the positive electrode is high or when the battery is exposed to high temperatures, and this deterioration phenomenon causes a problem of deterioration in the cycle characteristics of the secondary battery.
[0006] In addition, when a lithium-ion battery is used continuously for a long time or left at high temperatures, gas is generated and the thickness of the battery increases, which is called the swelling phenomenon. It is known that the amount of gas generated at this time depends on the state of the SEI.
[0007] Therefore, in order to solve these problems, research and development efforts are being conducted on methods that can suppress the dissolution of metal ions in the positive electrode, form a stable SEI film on the negative electrode, reduce the swelling phenomenon of secondary batteries, and increase stability at high temperatures. Summary of the Invention [Problem to be solved by the invention]
[0008] As a result of conducting research from various angles to solve the above problems, an object of the present invention is to provide a nonaqueous electrolyte having improved stability at high temperatures by including a nonaqueous electrolyte that can suppress deterioration of a positive electrode, reduce side reactions between a positive electrode and an electrolyte, and form a stable SEI film on a negative electrode.
[0009] That is, an object of the present invention is to provide a lithium secondary battery containing the non-aqueous electrolyte, which has improved high-temperature cycle characteristics, high-temperature storage characteristics, and thermal stability, and thus has improved performance. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides a non-aqueous electrolyte comprising a lithium salt, an organic solvent, a compound represented by the following Chemical Formula 1 as a first additive, and a compound represented by the following Chemical Formula 2 or 3 as a second additive:
[0011] [ka]
[0012] In the above Chemical Formula 1, R1 to R3 are each independently H or -N=C=O, at least one of R1 to R3 is -N=C=O, and a and b are each an integer of 0 to 4.
[0013] [ka]
[0014] In the above chemical formula 2, R is a substituted or unsubstituted alkylene group having 1 to 3 carbon atoms, and R4 to R6 are each independently H, an alkyl group having 1 to 3 carbon atoms, or a nitrile group.
[0015] [ka]
[0016] In the above Chemical Formula 3, R7 is an alkylene group having 1 to 8 carbon atoms, and R8 is selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
[0017] The present invention also provides a lithium secondary battery containing the non-aqueous electrolyte. Effect of the Invention
[0018] The compound of Formula 1 provided as the first additive for the non-aqueous electrolyte of the present invention is a compound having three or more substituted isocyanate functional groups, and has a large number of film-forming sites, so that it can form a strong SEI (Solid Electrolyte Interphase) film, thereby suppressing the decrease in passivation ability of the SEI at high temperatures and preventing the deterioration of the negative electrode.
[0019] The compound of Formula 2 or Formula 3 provided as the second additive for the non-aqueous electrolyte of the present invention contains a propargyl group in the molecule, which helps improve high-temperature durability. The SEI film formed by the anode reduction reaction of the compound of Formula 2 or Formula 3 contains a propargyl group, which becomes a cross-link site in the SEI and allows additional reactions. When the additional cross-linking reaction proceeds, a strong SEI film is formed, which is effective in suppressing performance degradation due to anode electrodeposition of transition metals dissolved from the positive electrode. In addition, the cyclic carbonate functional group and imidazole functional group contained in the additive of Formula 2 or Formula 3 can effectively suppress side reactions on the positive electrode surface and deterioration of the positive electrode by forming a stable CEI, improving performance, and reducing the dissolution of transition metals that may occur during high-voltage charging. That is, the compound of Formula 2 or Formula 3 provided as the second additive for the non-aqueous electrolyte of the present invention can form a stable ion-conductive film on the surface of the positive electrode / negative electrode.
[0020] In addition, the first additive contains an isocyanate functional group, which is effective in scavenging moisture and HF in the electrolyte, and forms a polyurea- and polyurethane-based coating on the surface of the positive electrode / negative electrode. Such a polymeric coating can be formed more stably and strongly, especially when used together with a propargyl-based additive such as those represented by formulas 2-3. This is because a propargyl-based coating is formed between the polymeric coatings, which helps to strongly link the surfaces of the positive electrode / negative electrode. In addition, the propargyl-based additive exists in the polymer structure and acts as a linker between the polymeric coatings caused by the first additive. Therefore, the lithium secondary battery including the nonaqueous electrolyte of the present invention can suppress additional side reactions and reduce performance degradation even if volume expansion of the negative electrode occurs during charging and discharging due to the presence of a stable coating. Therefore, the nonaqueous electrolyte of the present invention can form an electrode-electrolyte interface that is stable and highly durable even at high temperatures, and can suppress unnecessary electrolyte decomposition side reactions, thereby realizing a lithium secondary battery with improved performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0022] As used herein, terms such as "comprise," "comprise," or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but should not be understood as precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0023] In the present specification, in the description of "number of carbon atoms a to b", "a" and "b" refer to the number of carbon atoms contained in a specific functional group. That is, the functional group may contain "a" to "b" carbon atoms. For example, "an alkylene group having 1 to 5 carbon atoms" refers to an alkylene group having 1 to 5 carbon atoms, i.e., -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH3)CH-, -CH(CH3)CH2-, and -CH(CH3)CH2CH2-.
[0024] In addition, in this specification, the term "alkylene group" means a branched or unbranched divalent hydrocarbon group.
[0025] In addition, in this specification, any alkyl group may be substituted or unsubstituted. The term "substituted" means that at least one hydrogen bonded to a carbon atom is substituted with an element other than hydrogen, and means that, for example, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, a heterocycloalkyl group having 3 to 12 carbon atoms, a heterocycloalkenyl group having 3 to 12 carbon atoms, an aryloxy group having 6 to 12 carbon atoms, a halogen atom, a fluoroalkyl group having 1 to 20 carbon atoms, a nitro group, an aryl group having 6 to 20 carbon atoms, a heteroaryl group having 2 to 20 carbon atoms, a haloaryl group having 6 to 20 carbon atoms, etc. are substituted.
[0026] The present invention will now be described in more detail.
[0027] Nonaqueous electrolyte The non-aqueous electrolyte according to the present invention may include a lithium salt, an organic solvent, a compound represented by the following Chemical Formula 1 as a first additive, and a compound represented by the following Chemical Formula 2 or 3 as a second additive.
[0028] The non-aqueous electrolyte according to the present invention includes a compound represented by the following formula 1 as a first additive. The compound represented by the following formula 1 is a compound in which three or more isocyanate functional groups are substituted, and since there are many sites capable of forming a film, it is possible to form a strong SEI (Solid Electrolyte Interphase) film. In addition, the isocyanate group scavenges moisture in the electrolyte, thereby suppressing an increase in acidity and improving durability. The first additive forms a polymeric film such as polyurea and polyurethane on the surface of the positive electrode / negative electrode.
[0029] [ka]
[0030] In the above Chemical Formula 1, R1 to R3 are each independently H or -N=C=O, and at least one of R1 to R3 is -N=C=O.
[0031] In the above chemical formula 1, a and b are each an integer of 0 to 4, and preferably an integer of 1 or 2.
[0032] Specifically, the compound of Formula 1 may be any one of the compounds represented by the following Formulas 1-1 to 1-4.
[0033] [ka]
[0034] [ka]
[0035] [ka]
[0036] [ka]
[0037] The nonaqueous electrolyte according to the present invention includes a compound represented by the following formula 2 or 3 as a second additive. The compound represented by formula 2 or 3 is easily reduced on the surface of the negative electrode due to the inclusion of a propargyl group, and can easily form a coating on the surface of the negative electrode. This coating has the advantages of being more stable than an SEI coating formed by the reductive decomposition of a typical electrolyte, having low electronic conductivity to suppress additional electrolyte decomposition reactions, and being less susceptible to damage caused by volumetric changes in the negative electrode. That is, by using the compound represented by formula 2 or 3 as an additive to the electrolyte, the stability of the interface between the negative electrode and the electrolyte can be ensured.
[0038] The compound of formula 2 contains a propargyl group having a triple bond, which is known to have metal ion adsorption properties, and an oxygen atom. The propargyl group, which is separated by the bond cleavage between the nitrogen (N) atom and the carbon (C) atom of the imidazole group, adsorbs metal foreign matter such as Fe, Co, Mn, and Ni that is dissolved from the positive electrode during high-voltage charging, and can effectively suppress the negative electrode deterioration phenomenon that occurs when these metal foreign matter is electrodeposited on the surface of the negative electrode. In addition, the compound represented by formula 2 can form a stable ion-conducting coating on the surface of the negative electrode because the lone pair of the nitrogen (N) atom of the imidazole group reacts with alkyl carbonate, which is a decomposition product of ethylene carbonate (EC) used as an organic solvent, and is reduced on the surface of the negative electrode. Therefore, not only can additional electrolyte decomposition reactions during charging and discharging be suppressed, but also the absorption and release of lithium ions from the negative electrode can be facilitated even during overcharging or high-temperature storage, improving the cycle life characteristics and high-temperature storage performance of the secondary battery.
[0039] [ka]
[0040] In the above chemical formula 2, R is a substituted or unsubstituted alkylene group having 1 to 3 carbon atoms, and R4 to R6 are each independently H, an alkyl group having 1 to 3 carbon atoms, or a nitrile group. Examples of the substituent of R include F and CF3.
[0041] Specifically, the compound of the present invention represented by Chemical Formula 2 may be a compound represented by the following Chemical Formula 2-1:
[0042] [ka]
[0043] The compound of formula 3 contains an ester functional group and an unsaturated hydrocarbon group in its molecular structure, and is decomposed before other electrolyte components during the initial charging process of the secondary battery, forming a coating on the surface of the negative electrode that is mainly composed of a carbon-oxygen single bond (CO) or carbon-oxygen double bond (C=O) based compound. Furthermore, the compound of formula 3 contains a propargyl group, which makes it easy to reduce on the surface of the negative electrode, and can easily form a coating on the surface of the negative electrode. This coating has the advantages of being more stable than SEI coatings formed by the reductive decomposition of general electrolytes, having low electronic conductivity to suppress additional electrolyte decomposition reactions, and being less damaged by volume changes in the negative electrode.
[0044] [ka]
[0045] In the above chemical formula 3, R7 may be an alkylene group having 1 to 8 carbon atoms, and preferably an alkylene group having 1 to 5 carbon atoms.
[0046] In the above Chemical Formula 3, R8 may be selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
[0047] The compound of Formula 3 may be a compound of Formula 3-1 below.
[0048] [ka]
[0049] In the above chemical formula 3-1, n may be a natural number of 1 to 8, preferably a natural number of 1 to 5, and most preferably a natural number of 1 to 3.
[0050] In the above chemical formula 3-1, R8 is H or an alkyl group having 1 to 10 carbon atoms, and is preferably H or a methyl group.
[0051] Specifically, the compound of the present invention represented by Chemical Formula 3 may be a compound represented by the following Chemical Formula 3-2:
[0052] [ka]
[0053] The first additive contained in the non-aqueous electrolyte of the present invention contains an isocyanate functional group, and thus forms a polyurea- and polyurethane-based coating on the surface of the positive electrode / negative electrode. Such a polymeric coating can be formed more stably and strongly, especially when used together with a propargyl-based additive such as those represented by Chemical Formulae 2-3. This is because a propargyl-based coating is formed between the polymeric coatings, which helps to strongly link the surfaces of the positive electrode / negative electrode. In addition, the propargyl-based additive exists in the polymer structure and acts as a linker between the polymeric coatings caused by the first additive. Therefore, the lithium secondary battery including the non-aqueous electrolyte of the present invention can suppress additional side reactions and reduce performance degradation even if the volume expansion of the negative electrode occurs during charging and discharging due to the presence of a stable coating. Therefore, the non-aqueous electrolyte of the present invention can form an electrode-electrolyte interface that is stable and highly durable even at high temperatures, and can suppress unnecessary electrolyte decomposition side reactions, thereby realizing a lithium secondary battery with improved performance.
[0054] In the non-aqueous electrolyte according to the present invention, the first additive may be contained in an amount of 0.01 to 5 parts by weight, preferably 0.05 to 3.0 parts by weight, and more preferably 0.10 to 2.0 parts by weight, per 100 parts by weight of the non-aqueous electrolyte. When the content of the first additive is within the above range, the effect of forming a coating on the negative electrode is sufficient, and there is an effect of excellent life characteristics at high temperatures and high-temperature storage characteristics.
[0055] In the non-aqueous electrolyte according to the present invention, the second additive may be contained in an amount of 0.01 to 5 parts by weight, preferably 0.05 to 3.0 parts by weight, and more preferably 0.10 to 2.5 parts by weight, per 100 parts by weight of the non-aqueous electrolyte. When the content of the first additive is within the above range, the effect of forming a coating on the negative electrode is sufficient, and there is an effect of excellent high-temperature life characteristics and high-temperature storage characteristics.
[0056] In the nonaqueous electrolyte of the present invention, the first additive and the second additive may be included in a weight ratio of 1:0.002 to 1:500, preferably a weight ratio of 1:0.01 to 1:300, and most preferably a weight ratio of 1:0.02 to 1:250. When the above range is satisfied, the elasticity of the SEI coating falls within an appropriate range, and the SEI coating can be firmly maintained during charge and discharge or at high temperatures.
[0057] The non-aqueous electrolyte according to the present invention may contain a lithium salt. The lithium salt is used as an electrolyte salt in a lithium secondary battery and is used as a medium for transferring ions. Generally, the lithium salt contains, for example, Li as a cation. + and as an anion, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO2- , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - , and SCN - At least one selected from the group consisting of:
[0058] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiSO3CF3, LiCO2CH3, LiCO2CF3, LiAsF6, LiSbF6, LiSO3CH3, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide; LiFSI), LiN(SO2CF2CF3)2 (lithium bis(perfluoroethanesulfonyl)imide; LiBETI), and LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide; LiTFSI). In addition to these, lithium salts commonly used in electrolytes for lithium secondary batteries can be used without any restrictions.
[0059] The lithium salt may be appropriately changed within a range that is normally usable, but in order to obtain an optimal effect of forming a corrosion prevention coating on the electrode surface, it may be contained in the electrolyte at a concentration of 0.5 M to 5.0 M, preferably a concentration of 1.0 M to 3.0 M, and more preferably a concentration of 1.2 M to 2.0 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics during high-temperature storage of the lithium secondary battery is sufficient, and the viscosity of the non-aqueous electrolyte is appropriate, so that the electrolyte impregnation can be improved.
[0060] The non-aqueous electrolyte according to the present invention may include an organic solvent, which may include at least one organic solvent selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, and a cyclic ester organic solvent.
[0061] The additive of the present invention is particularly effective when a cyclic carbonate solvent is used. When a conventional electrolyte additive is used together with a cyclic carbonate solvent, the SEI film formed by decomposition of the cyclic carbonate solvent is difficult to maintain due to the volume change of the negative electrode that occurs as the cycle progresses, and the decomposition of the solvent continues. This causes a problem that the ionic conductivity of the electrolyte decreases and the cycle characteristics deteriorate. However, when a combination of the additive of the present invention is used together with a cyclic carbonate solvent, a strong SEI film can be formed, and the cycle characteristics can be maintained at a high level.
[0062] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and therefore easily dissociates the lithium salt in the electrolyte. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and among these, fluoroethylene carbonate (FEC) may be included.
[0063] The linear carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and a representative example thereof may be at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and may include diethyl carbonate (DEC).
[0064] In addition, in order to produce an electrolyte having high ionic conductivity, the organic solvent may further contain at least one or more ester-based organic solvents selected from the group consisting of linear ester-based organic solvents and cyclic ester-based organic solvents in addition to the at least one or more carbonate-based organic solvents selected from the group consisting of cyclic carbonate-based organic solvents and linear carbonate-based organic solvents.
[0065] Specific examples of such linear ester-based organic solvents include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0066] The cyclic ester organic solvent may be at least one organic solvent selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0067] Meanwhile, the organic solvent may be, if necessary, an organic solvent that is generally used in non-aqueous electrolytes without limitation, and may further include at least one of an ether-based organic solvent, a glyme-based solvent, and a nitrile-based organic solvent.
[0068] The ether solvent may be any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL), and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more of these, but is not limited thereto.
[0069] The glyme-based solvent has a higher dielectric constant and lower surface tension than linear carbonate-based organic solvents and is less reactive with metals, and may include at least one selected from the group consisting of dimethoxyethane (glyme, DME), diethoxyethane, diglyme, triglyme, and tetraglyme (TEGDME), but is not limited thereto.
[0070] The nitrile-based solvent may be one or more selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, but is not limited thereto.
[0071] In addition, the nonaqueous electrolyte of the present invention may further contain a known electrolyte additive, as necessary, in order to prevent the nonaqueous electrolyte from being decomposed in a high-output environment, which would cause the collapse of the negative electrode, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and the effect of suppressing battery expansion at high temperatures.
[0072] Representative examples of such other electrolyte additives may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0073] The cyclic carbonate compounds include vinylene carbonate (VC) and vinyl ethylene carbonate.
[0074] An example of the halogen-substituted carbonate compound is fluoroethylene carbonate (FEC).
[0075] The sultone compound includes at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0076] The sulfate compounds include ethylene sulfate (Esa), trimethylene sulfate (TMS), and methyl trimethylene sulfate (MTMS).
[0077] The phosphate-based compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(2,2,2-trifluoroethyl)phosphite.
[0078] Examples of the borate-based compounds include tetraphenylborate, lithium difluoro(oxalate)borate (LiODFB), and lithium bisoxalateborate (LiB(C2O4)2, LiBOB).
[0079] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0080] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.
[0081] The lithium salt-based compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, and examples of the lithium salt-based compound include lithium difluorophosphate (LiDFP), LiPO2F2, and LiBF4.
[0082] Among these other electrolyte additives, when a combination of vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (Esa), and lithium difluorophosphate (LiDFP) is further included, a stronger SEI film can be formed on the surface of the negative electrode during the initial activation process of the secondary battery, and the generation of gas that may be generated by decomposition of the electrolyte at high temperatures can be suppressed, thereby improving the high temperature stability of the secondary battery.
[0083] Meanwhile, the other electrolyte additives may be used in combination of two or more kinds, and may be included in an amount of 0.050 wt% to 20 wt%, specifically 0.10 wt% to 15 wt%, and preferably 0.30 wt% to 10 wt%, based on the total weight of the non-aqueous electrolyte. When the content of the other electrolyte additives satisfies the above range, a more excellent effect of improving ion conductivity and cycle characteristics can be obtained.
[0084] Lithium secondary battery The present invention also provides a lithium secondary battery containing the non-aqueous electrolyte.
[0085] Specifically, the lithium secondary battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and the non-aqueous electrolyte.
[0086] In this regard, the lithium secondary battery of the present invention may be manufactured by a conventional method known in the art, for example, by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator are sequentially stacked between the positive electrode and the negative electrode, and then inserting the electrode assembly into a battery case and injecting the non-aqueous electrolyte according to the present invention into the battery case.
[0087] (1) Positive electrode The positive electrode may be prepared by coating a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, and a solvent on a positive electrode current collector.
[0088] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. may be used.
[0089] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specifically, it may include lithium metal oxides containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium metal oxide may be a lithium-manganese-based oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-manganese-cobalt-based oxide (e.g., Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.), or a lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mnr2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are atomic fractions of independent elements, respectively, with 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc.) etc. may be mentioned, and any one or two or more of these compounds may be included.
[0090] Among them, from the viewpoint of being able to enhance the capacity characteristics and stability of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), etc. may be used, and any one or two or more of these mixtures may be used.
[0091] Among them, from the viewpoint of being able to enhance the capacity characteristics of the battery most, a positive electrode active material with a nickel content of 80 atm% or more can be used. For example, the lithium transition metal oxide may include those represented by the following Chemical Formula 4.
[0092] [Chemical Formula 4] Li x Ni a Co b M 1 c M 2d O2
[0093] In the above Chemical Formula 4, M 1 is one or more selected from Mn and Al, and may be preferably Mn or a combination of Mn and Al from the viewpoint of durability.
[0094] M 2 may be one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.
[0095] The x represents the atomic fraction of lithium in the lithium transition metal oxide, and may be 0.90≦x≦1.1, preferably 0.95≦x≦1.08, and more preferably 1.0≦x≦1.08.
[0096] The a represents the atomic fraction of nickel among the metal elements other than lithium in the lithium transition metal oxide, and may be 0.80≦a<1.0, preferably 0.80≦a≦0.95, and more preferably 0.80≦a≦0.90. When the nickel content satisfies the above range, high capacity characteristics can be achieved.
[0097] The b represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium transition metal oxide, and is 0. <b<0.2、0<b≦0.15、または0.01≦b≦0.10であってよい。
[0098] The c is M among the metal elements other than lithium in the lithium transition metal oxide. 1 represents the atomic fraction of 0 <c<0.2、0<c≦0.15、または0.01≦c≦0.10であってよい。
[0099] The d is the number of metal elements other than lithium in the lithium transition metal oxide, M 2 and may be 0≦d≦0.1, or 0≦d≦0.05.
[0100] The positive electrode active material may be contained in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solids excluding the solvent in the positive electrode mixture slurry.
[0101] The binder is a component that assists in binding the active material and conductive material and the like to the current collector.
[0102] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.
[0103] Typically, the binder may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids in the positive electrode mixture slurry excluding the solvent.
[0104] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1% by weight to 20% by weight based on the total weight of the solid content in the negative electrode slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powder such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.
[0105] Typically, the conductive material may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode mixture slurry.
[0106] The solvent may contain an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the positive electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the solvent may be contained so that the concentration of the solid content including the positive electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, preferably 70% by weight to 95% by weight, and more preferably 70% by weight to 90% by weight.
[0107] (2) Negative electrode The negative electrode can be prepared by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode current collector, or a graphite electrode made of carbon (C) or a metal itself can be used as the negative electrode.
[0108] For example, when the negative electrode is manufactured by coating the negative electrode mixture slurry on the negative electrode current collector, the negative electrode current collector generally has a thickness of 3 μm to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, as with the positive electrode current collector, the binding force of the negative electrode active material may be strengthened by forming fine irregularities on the surface, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric body, etc.
[0109] Further, the negative electrode active material may contain at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of these metals and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0110] The carbon material capable of reversibly intercalating / deintercalating lithium ions can be used without particular limitation as long as it is a carbon-based negative electrode active material generally used in lithium ion secondary batteries. Representative examples thereof include crystalline carbon, amorphous carbon, or a combination of these. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite. Examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, and calcined coke.
[0111] As the metal or an alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium can be used.
[0112] Examples of the metal composite oxide include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Group 1, Group 2, Group 3 of the periodic table, halogen; 0 <x≦1; 1≦y≦3; 1≦z≦8) can be used.
[0113] Examples of the substance capable of doping and undoping lithium include Si, SiO x (0 < x ≤ 2), Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), etc. Further, at least one of these may be mixed with SiO2 and used. The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0114] Examples of the transition metal oxide include lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.
[0115] The additive according to the present invention is particularly effective when Si or SiO x (0 < x ≤ 2) is used as the negative electrode active material. Specifically, when using an Si-based negative electrode active material, if a strong SEI layer is not formed on the surface of the negative electrode during initial activation, the life characteristics will be promoted to decline due to intense volume expansion and contraction during the cycle. However, the additive according to the present invention can form a strong SEI layer while having elasticity, so that a secondary battery using an Si-based negative electrode active material can have excellent life characteristics and storage characteristics.
[0116] The negative electrode active material may be contained in an amount of 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, more preferably 80% by weight to 98% by weight, based on the total weight of the solid content in the negative electrode mixture slurry.
[0117] Examples of the binder include polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers thereof, etc. Specifically, styrene-butadiene rubber (SBR)-carboxymethyl cellulose (CMC) can be used because of its high viscosity.
[0118] Typically, the binder may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.
[0119] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1% by weight to 20% by weight based on the total weight of the solid content in the negative electrode mixture slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powder such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives.
[0120] The conductive material may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.
[0121] The solvent may include water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the negative electrode active material, and optionally a binder and a conductive material, etc. are included. For example, the solvent may be included so that the concentration of the solid content including the negative electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, preferably 70% by weight to 90% by weight.
[0122] When a metal is used as the negative electrode, the negative electrode can be manufactured by physically bonding, rolling, or depositing a metal on a metal thin film or the negative electrode current collector. The deposition method can be an electrical deposition or chemical vapor deposition method.
[0123] For example, the metal thin film itself or the metal bonded / rolled / deposited onto the negative electrode current collector may include one metal or an alloy of two metals selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu), and indium (In).
[0124] (3) Separator The separator may be a conventional porous polymer film, such as a porous polymer film made of a polyolefin polymer, such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, which is used alone or in a laminated state, or a conventional porous nonwoven fabric, such as a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, etc., may be used, but is not limited thereto. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or a multilayer structure.
[0125] Specifically, the separator included in the electrode assembly of the present invention may be a safety reinforced separator (SRS) having a coating layer containing a ceramic component or a polymeric material formed thereon to ensure heat resistance or mechanical strength.
[0126] Specifically, the separator included in the electrode assembly of the present invention may include a porous separator substrate and a porous coating layer that is entirely coated on one or both sides of the separator substrate. The coating layer may include a mixture of inorganic particles selected from a metal oxide, a metalloid oxide, a metal fluoride, a metal hydroxide, and combinations thereof, and a binder polymer that connects and fixes the inorganic particles to each other.
[0127] The coating layer may contain one or more inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, and MgF. Here, the inorganic particles can improve the thermal stability of the separator. That is, the inorganic particles can prevent the separator from shrinking at high temperatures. And the binder polymer can fix the inorganic particles and improve the mechanical stability of the separator.
[0128] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0129] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely illustrative for understanding the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description, and it goes without saying that such changes and modifications belong to the scope of the attached claims.
[0130] Working Example Example 1 (Production of non-aqueous electrolyte) LiPF6 was dissolved in an organic solvent (ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 20: 80 volume ratio) to a concentration of 1.2 M to prepare a non-aqueous solvent, and 0.01 g of a compound represented by the following Formula 1-1 and 0.01 g of a compound represented by the following Formula 2-1 were added to 99.98 g of the non-aqueous solvent to prepare a non-aqueous electrolyte.
[0131] [ka]
[0132] [ka]
[0133] (manufacturing lithium secondary batteries) Cathode active material (LiNi 0.85 Co 0.05 Mn 0.08 Al 0.02 A cathode slurry (solid content 75.5 wt%) was prepared by adding the cathode material (O2), conductive material (carbon nanotubes), and binder (polyvinylidene fluoride) in a weight ratio of 97.74:0.7:1.56 to the solvent N-methyl-2-pyrrolidone (NMP). The cathode slurry was applied to one side of a cathode current collector (aluminum thin film) with a thickness of 15 μm, and dried and roll pressed to prepare a cathode.
[0134] A negative electrode active material (silicon; Si), a conductive material (carbon black), and a binder (styrene-butadiene rubber (SBR)-carboxymethyl cellulose (CMC)) were added to a solvent, N-methyl-2-pyrrolidone (NMP), in a weight ratio of 70:20.3:9.7 to prepare a negative electrode slurry (solid content 26% by weight). The negative electrode slurry was applied to one side of a negative electrode current collector (Cu thin film) with a thickness of 15 μm, and dried and roll pressed to prepare a negative electrode.
[0135] In a dry room, a polyolefin-based porous separator coated with inorganic particles Al2O3 was interposed between the positive electrode and the negative electrode prepared above, and then the non-aqueous electrolyte prepared above was injected to prepare a secondary battery.
[0136] Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared by adding 0.01 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 3-2 below to 99.98 g of the non-aqueous solvent prepared in Example 1.
[0137] [ka]
[0138] Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that 0.01 g of the compound of Formula 1-1 and 5 g of the compound of Formula 2-1 were added to 94.99 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0139] Example 4 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared by adding 0.01 g of the compound of Formula 1-1 and 5 g of the compound of Formula 3-2 to 94.99 g of the non-aqueous solvent prepared in Example 1.
[0140] Example 5 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 2-1 were added to 94.99 g of the nonaqueous solvent manufactured in Example 1 to prepare a nonaqueous electrolyte.
[0141] Example 6 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 3-2 were added to 94.99 g of the nonaqueous solvent manufactured in Example 1 to prepare a nonaqueous electrolyte.
[0142] Example 7 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 1-1 and 5 g of the compound of Formula 2-1 were added to 90 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0143] Example 8 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 1-1 and 5 g of the compound of Formula 3-2 were added to 90 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0144] Example 9 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared by adding 0.01 g of the compound represented by the following Formula 1-2 and 0.01 g of the compound represented by the following Formula 2-1 to 99.98 g of the non-aqueous solvent prepared in Example 1.
[0145] [ka]
[0146] Example 10 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared by adding 0.01 g of a compound represented by the following Formula 1-3 and 0.01 g of a compound represented by the following Formula 2-1 to 99.98 g of the non-aqueous solvent prepared in Example 1.
[0147] [ka]
[0148] Example 11 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared by adding 0.01 g of the compound represented by the following Formula 1-4 and 0.01 g of the compound represented by the following Formula 2-1 to 99.98 g of the non-aqueous solvent prepared in Example 1.
[0149] [ka]
[0150] Comparative Example 1 A secondary battery was manufactured in the same manner as in Example 1, except that 0.01 g of the compound of Formula 1-1 was added to 99.99 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0151] Comparative Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 1-1 was added to 95 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0152] Comparative Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that 0.01 g of the compound of Formula 2-1 was added to 99.99 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0153] Comparative Example 4 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 2-1 was added to 95 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0154] Comparative Example 5 A secondary battery was manufactured in the same manner as in Example 1, except that 0.01 g of the compound of Formula 3-2 was added to 99.99 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0155] Comparative Example 6 A secondary battery was manufactured in the same manner as in Example 1, except that 5 g of the compound of Formula 3-2 was added to 95 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0156] Experimental Example 1: Evaluation of high temperature cycle characteristics The cycle characteristics of each of the secondary batteries produced in Examples 1 to 11 and Comparative Examples 1 to 6 were evaluated.
[0157] Specifically, each of the batteries manufactured in Examples 1 to 11 and Comparative Examples 1 to 6 was charged at 45° C. under constant current / constant voltage conditions at a rate of 0.33 C to 4.2 V (0.05 C cut off), and discharged at a constant current of 0.33 C to 3.0 V, which constitutes one cycle. After 200 cycles of charge and discharge, the capacity retention rate after 200 cycles relative to the initial capacity after 1 cycle was measured. In addition, the resistance increase rate after 200 cycles relative to the initial resistance after 1 cycle was measured. The results are shown in Table 1 below.
[0158] [Table 1]
[0159] Experimental Example 2: Evaluation of high-temperature storage characteristics For each of the secondary batteries produced in Examples 1 to 11 and Comparative Examples 1 to 6, high-temperature storage characteristics were evaluated.
[0160] Specifically, each of the secondary batteries of Examples 1 to 11 and Comparative Examples 1 to 6 was fully charged to 4.2 V and then stored at 60° C. for 8 weeks.
[0161] Before storage, the capacity of the fully charged secondary battery was measured and set as the initial capacity of the secondary battery.
[0162] After 8 weeks, the capacity of the stored secondary battery was measured, and the capacity loss during the 8-week storage period was calculated. The percentage of the loss in capacity relative to the initial capacity of the secondary battery was calculated to derive the capacity retention rate after 8 weeks. In addition, the percentage of the increase in resistance relative to the initial resistance of the secondary battery was calculated to derive the resistance increase rate after 8 weeks. The results are shown in Table 2 below.
[0163] [Table 2]
[0164] Experimental Example 3 - Evaluation of thermal stability The thermal stability of each of the secondary batteries produced in Examples 1 to 11 and Comparative Examples 1 to 6 was evaluated.
[0165] Specifically, the lithium secondary batteries manufactured in the examples and comparative examples were subjected to an activation process, and then charged at 25°C at a rate of 0.33C up to 4.2V under constant current / constant voltage conditions (0.05C cut off) and fully charged to SOC100%. The fully charged batteries were heated to 140°C at a heating rate of 5°C / min, and then left for 1 hour, and a hot box evaluation experiment was performed to check for the presence or absence of ignition. Cases where no ignition occurred were evaluated as Pass, and cases where ignition occurred were evaluated as Fail, and the results are shown in Table 3 below.
[0166] [Table 3]
Claims
1. A lithium salt; An organic solvent; A compound represented by the following formula 1 as a first additive, A non-aqueous electrolyte comprising a compound represented by the following formula 2 or 3 as a second additive: 【Chemistry 1】 (In the above Chemical Formula 1, R 1 ~R 3 are each independently H or -N=C=O, R 1 ~R 3 At least one of is -N=C=O; a and b are each an integer from 0 to 4; 【Chemistry 2】 In the above Chemical Formula 2, R is a substituted or unsubstituted alkylene group having 1 to 3 carbon atoms; R 4 ~R 6 are each independently H, an alkyl group having 1 to 3 carbon atoms, or a nitrile group; 【Chemistry 3】 In the above Chemical Formula 3, R 7 is an alkylene group having 1 to 8 carbon atoms, R 8 is selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
2. The non-aqueous electrolyte according to claim 1 , wherein the compound of the formula 1 is any one selected from the following formulas 1-1 to 1-4: 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】
3. The non-aqueous electrolyte according to claim 1, wherein the compound of Chemical Formula 2 is a compound of Chemical Formula 2-1 below. 【Chemistry 8】
4. The non-aqueous electrolyte according to claim 1, wherein the compound of Chemical Formula 3 is a compound of Chemical Formula 3-1 below. 【Chemistry 9】 (In the above Chemical Formula 3-1, The n is a natural number from 1 to 8, R 8 is H or an alkyl group having 1 to 10 carbon atoms.
5. The non-aqueous electrolyte according to claim 1, wherein the compound of Chemical Formula 3 is a compound of Chemical Formula 3-2 below. 【Chemistry 10】
6. The non-aqueous electrolyte of claim 1 , wherein the first additive is present in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the non-aqueous electrolyte.
7. The non-aqueous electrolyte of claim 1 , wherein the second additive is present in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the non-aqueous electrolyte.
8. The non-aqueous electrolyte according to claim 1 , wherein the first additive and the second additive are contained in a weight ratio of 1:0.002 to 1:
500.
9. The lithium salts are LiCl, LiBr, LiI, and LiBF. 4 , LiClO 4 , LiB 10 C 10 , LiAlCl 4 , LiAlO 2 , LiPF 6 , LiSO 3 CF 3 , LiCO 2 CH 3 , LiCO 2 CF 3 , LiAsF 6 , LiSbF 6 , LiSO 3 CH 3 , LiN(SO 2 F) 2 , LiN(SO 2 CF 2 CF 3 ) 2 , and LiN(SO 2 CF 3 ) 2 The non-aqueous electrolyte according to claim 1 , wherein the non-aqueous electrolyte is one or more selected from the group consisting of:
10. The non-aqueous electrolyte according to claim 1 , wherein the lithium salt is contained at a concentration of 0.5 M to 5.0 M.
11. 2. The nonaqueous electrolyte according to claim 1, wherein the organic solvent includes at least one organic solvent selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, and a cyclic ester organic solvent.
12. A positive electrode and A negative electrode; A lithium secondary battery comprising the nonaqueous electrolyte according to claim 1 .
13. The lithium secondary battery according to claim 12, wherein the positive electrode contains a lithium nickel-based oxide as a positive electrode active material, the lithium nickel-based oxide having a nickel content of 80 atm % or more among transition metals other than lithium.
14. The method for producing a lithium secondary battery according to claim 13, wherein the lithium nickel-based oxide is represented by the following chemical formula 4: [Chemical formula 4] Li a Ni b Co c M 1 d M 2 e O 2 (In the above Chemical Formula 4, M 1 is Mn, Al, or a combination thereof; M 2 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0.8≦a≦1.2, 0.8≦b<1, 0<c<0.2, 0<d<0.2, and 0≦e≦0.1.)
15. The negative electrode contains Si and SiO as a negative electrode active material. x The lithium secondary battery according to claim 12, comprising at least one selected from the group consisting of (0<x≦2).
Citation Information
Patent Citations
Electrolyte and preparation method and application thereof
CN113381071A
Battery and electrolyte composition
JP2007242411A
Nonaqueous electrolyte for secondary battery, and nonaqueous electrolyte secondary battery including the same
JP2012182131A
Nonaqueous electrolyte and lithium secondary battery using the same
JP2013175369A
Electrolyte for lithium secondary battery and lithium secondary battery including the same
JP2022521585A